2020
DOI: 10.3390/jimaging6080077
|View full text |Cite
|
Sign up to set email alerts
|

Structural Similarity Measurement Based Cost Function for Stereo Matching of Automotive Applications

Abstract: The human visual perception uses structural information to recognize stereo correspondences in natural scenes. Therefore, structural information is important to build an efficient stereo matching algorithm. In this paper, we demonstrate that incorporating the structural information similarity, extracted either from image intensity (SSIM) directly or from image gradients (GSSIM), between two patches can accurately describe the patch structures and, thus, provides more reliable initial cost values. We also addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Study [Weg09] has shown that a mixture of census or rank transforms with the simple sum of absolute differences (SAD) or sum of squared differences (SSD) can be very efficient for such multiview sequences. [Zeg20] proves that the use of structural similarity performs very well when radiometric distortions are present in processed input views.…”
Section: Related Workmentioning
confidence: 77%
“…Study [Weg09] has shown that a mixture of census or rank transforms with the simple sum of absolute differences (SAD) or sum of squared differences (SSD) can be very efficient for such multiview sequences. [Zeg20] proves that the use of structural similarity performs very well when radiometric distortions are present in processed input views.…”
Section: Related Workmentioning
confidence: 77%